PENDEKATAN FILSAFAT HUKUM ISLAM (URGENSITAS, APLIKASI, OPERASIONALISASI, DAN BENTUK SERTA KRITIK TERHADAP PERKEMBANGAN HUKUM ISLAM) - Ansori, Saiful (Institut Agama Islam Negeri (IAIN) Syekh Nurjati Cirebon, 2024)
AbstractStudying Islamic law certainly cannot be separated from the philosophy of Islamic law. Islamic law, which has always struggled with the realities of the times, has now been able to grow legal products in accordance with the current developments of the times. The focus of study in this research is to try to explain the study of legal philosophy, starting from the understanding of Islamic legal philosophy, the scope of Islamic legal philosophy studies, the urgency of Islamic legal philosophy, the application and operationalization of Islamic legal philosophy, as well as forms or examples of Islamic legal philosophy studies, as well as critics.The research method used in this research is qualitative. The approach used in this research is the socio-legal approach. Then combined with empirical and normative legal approaches. The data collection method used was the literature study method which was then analyzed using the descriptive-analytic method.The Islamic legal philosophy approach is needed for a more in-depth study of Islamic law. In order to realize just law that is always in accordance with the conditions of the times, the study of the philosophy of Islamic law also allows for a thorough understanding of Islam (kaffah) with the linkages and relationships that exist with other religious sciences. Islamic law must be oriented towards maqasid syari'ah, namely human benefit. Any reason cannot be justified if maqasid syari'ah as a legal goal is neglected, even though it has departed from a relatively correct interpretation. Islamic law is not independent, but related to other sciences. Therefore, interdependent relationships in the study of Islamic law are absolutely necessary to produce human-responsive law (fiqh).